Derivation of a multi-biomarker model and score as a predictor of 30-day mortality in critically ill sepsis patients: A prospective cohort study - Wan Shukeri, Wan Fadzlina; Md Ralib, Azrina; Abdullah, Nor Zamzila; Mat Nor, Mohd Basri (2017)
OBJECTIVE The objective of this study was to assess five biomarkers in sepsis: procalcitonin (PCT), interleukin-6 (IL-6), paraoxonase (PON) and arylesterase (ARE) activities of PON-1 and white blood cell (WBC) count in order to derive a multi-biomarker risk stratification model and score to predict 30-day mortality in critically ill patients with sepsis. METHODS This was a secondary analysis of a prospective, single-center, observational cohort performed in a 12-bed ICU in Hospital Tengku Ampuan Afzan, Pahang, Malaysia. There were 159 patients enrolled. Inclusion criteria: 1) adult patients of ≥18 years 2) presence of suspected or documented infection; and 3) a rise in SOFA score by 2 or more points. The five biomarkers were assayed within 24 hours of admission and subsequently at 24 and 48 hours later. Multivariable logistic regression was used to identify an optimal combination of biomarkers to create a panel. The derived formula for weighting biomarker values was used to calculate a “Sepsis Mortality Score,” which was the predicted probability of the primary outcome of 30-day mortality. RESULTS The primary outcome of 30-day mortality was reached in 46 (28.9%) of patients. Day 1 PCT, Day 3 IL-6 and Day 3 ARE were selected in the final step of the regression model. The AUC for the accuracy of the Sepsis Mortality Score derived from these three biomarkers was 0.83 (95% CI 0.74-0.91, P =0.000), suggesting very good model discrimination. When included in multivariate models with clinical variables, the score remained highly significant (p < 0.001) with an OR 25.63 (95% CI 5.45-120.56). CONCLUSIONS A biomarker panel of Day 1 PCT, Day 3 IL-6 and Day 3 ARE was predictive of 30-day mortality in critically ill patients with sepsis. Further study is warranted to prospectively validate the clinical utility of these biomarkers and the Sepsis Mortality Score in risk-stratifying patients with sepsis.